2014
DOI: 10.4103/0976-9668.136171
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS knowledge and its implications on dentists

Abstract: Aims and Objectives:The aim of the present study was to evaluate the knowledge of dentists regarding human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS).Materials and Methods:A structured questionnaire to evaluate the knowledge, fears, and attitudes was self administered to 102 dentists. The data was then evaluated using Chi-square test and a P < 0.05 was considered statistically significant.Results and Conclusion:The findings of the present study suggest that dentists in private practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…76.6% of dentists had a better knowledge than dental students -47.3% of knowledge score [19,23,24,28,31]. The anxiety of work-related exposure may explain the reason for such a negative attitude of the students for HIV/ AIDS patients.…”
Section: Assessment Of Knowledge and Attitudes Of Dentists And Dentalmentioning
confidence: 98%
See 3 more Smart Citations
“…76.6% of dentists had a better knowledge than dental students -47.3% of knowledge score [19,23,24,28,31]. The anxiety of work-related exposure may explain the reason for such a negative attitude of the students for HIV/ AIDS patients.…”
Section: Assessment Of Knowledge and Attitudes Of Dentists And Dentalmentioning
confidence: 98%
“…Previous studies indicate that an increase in the willingness to take care of HIV-infected patients occur when the knowledge of HIV also increases [17,18]. A total of 69.8% of the dentists reported that the lack of proper knowledge and training in handling HIV-infected patients were their main concerns in treating those patients [19]. There is also evidence that the changes of health professionals' attitudes toward HIV patients cannot occur by legal measures only.…”
Section: Assessment Of Knowledge and Attitudes Of Dentists And Dentalmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have been conducted on physicians, nurses and dentists to examine their knowledge about AIDS, attitudes towards these patients and willingness to treat them [5,6,7]. Minimal information can be found regarding this topic for physical therapists' or physical therapy students' in India.…”
Section: Introductionmentioning
confidence: 99%